Effect of Modern Tax Administration System, Tax Sanctions, Public Service Accountability and Trust Level in Government and Legal Systems in Sidoarjo City - Amalia Rosida; Herman Ernandi (Universitas Muhammadiyah Sidoarjo, 2022)
This study aims to determine the effect of modern tax administration systems, tax sanctions, public service accountability and the level of trust in the government and legal systems on motor vehicle taxpayer compliance studies at the Sidoarjo City Samsat Office. This study uses quantitative methods and the data used are data primary. The population in this study were motorized vehicle taxpayers registered at the Samsat Office of Sidoarjo City with a total sample of 100 respondents. Determination of the sample using the Incidental Sampling method. Collecting data in this study through the distribution of questionnaires. The analytical method used is multiple linear regression analysis with SPSS version 26 program. The results show that partially modern tax administration systems, tax sanctions, public service accountability and the level of trust in the government and legal systems affect the compliance of motorized vehicle taxpayers at the Samsat Office. City of Sidoarjo.